Linguistics and marketing: The effect of foreign languages in advertising messages - Alcántara-Pilar, Juan Miguel (2024)
In international advertising, foreign languages often serve symbolic purposes, each associated with distinct characteristics. This study explores whether recognizing the language in advertising messages influences the perceived image and Word-of-Mouth (WOM) for the company. Utilizing a between-subjects experimental design, we selected five languages as independent variables: Italian, Turkish, Russian, English, and French. An audio-only advertising message for a fictional company was created and translated into these languages. Native Spanish-speaking participants listened to the message in a foreign language and responded to inquiries about the advertised firm. The findings clearly demonstrate that recognizing the language has a significant impact on both company image and WOM. This underscores the nuanced role of language in shaping perceptions in international advertising. The study provides valuable insights into effective language choices for global advertising strategies, emphasizing the necessity of linguistic considerations beyond mere comprehension. Recognizing and leveraging the symbolic nature of languages can profoundly influence consumer perceptions and communication strategies across diverse linguistic contexts, contributing to the overall effectiveness of international advertising campaigns.